The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0190927
|View full text |Cite
|
Sign up to set email alerts
|

Localized zinc distribution in shark vertebrae suggests differential deposition during ontogeny and across vertebral structures

Abstract: The development of shark vertebrae and the possible drivers of inter- and intra-specific differences in vertebral structure are poorly understood. Shark vertebrae are used to examine life-history traits related to trophic ecology, movement patterns, and the management of fisheries; a better understanding of their development would be beneficial to many fields of research that rely on these calcified structures. This study used Scanning X-ray Fluorescence Microscopy to observe zinc distribution within vertebrae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 56 publications
(79 reference statements)
2
19
0
Order By: Relevance
“…Similarities also emerged among most of the species in their patterns of Mn and Zn concentrations, with both elements being elevated early in life followed by a decline. A similar pattern was observed for multiple shark species from Australia, including C. brevipinna, where Zn concentrations were very high pre-birth and declined post-birth (Raoult et al, 2018). The elevated Zn concentrations observed in the early life of all species in this study match the post-birth pattern observed by Raoult et al (2018), and we hypothesize that this may be the result of maternal loading.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarities also emerged among most of the species in their patterns of Mn and Zn concentrations, with both elements being elevated early in life followed by a decline. A similar pattern was observed for multiple shark species from Australia, including C. brevipinna, where Zn concentrations were very high pre-birth and declined post-birth (Raoult et al, 2018). The elevated Zn concentrations observed in the early life of all species in this study match the post-birth pattern observed by Raoult et al (2018), and we hypothesize that this may be the result of maternal loading.…”
Section: Discussionsupporting
confidence: 84%
“…Elements that are present in the environment are incorporated into the vertebral hydroxyapatite matrix during the biomineralization process, as the vertebrae grow concentrically over time. Although studies validating elemental uptake pathways into elasmobranch vertebrae are currently limited, concentrations of certain elements are thought to be associated with environmental variables such as salinity (Sr, Ba;Tillett et al, 2011) and temperature (Ba, Mg;Smith et al, 2013), dietary intake (Zn, Mn; Mathews and Fisher, 2009), maternal loading (Zn; Raoult et al, 2018), and unresolved physiological controls (McMillan et al, 2017). Consequently, chemical analysis of vertebrae sampled continuously along their radial growth axis may proxy how environmental conditions changed throughout an individual's life (Scharer et al, 2012;Smith et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of vertebral chemistry is one potential path forward, with elements such as strontium showing promise as a tool for shark ageing (Raoult, 2015; Raoult et al., 2016). Examination of other elements such as zinc may not be appropriate because the deposition of zinc appears to be highly variable within and between elasmobranch species and does not correlate with age for sawsharks (Raoult et al., 2018).…”
Section: Life Historymentioning
confidence: 99%
“…Several other assumptions also need to be addressed to confirm the suitability of vertebral elements as an environmental tracer, including the need to understand potential ontogenetic and diagenetic effects (see McMillan et al 2017a). In previous studies, vertebral element incorporation was not related to somatic growth or vertebral biomineralisation rates , with the exception of Zn : Ca (Raoult et al 2018). However, ontogeny and biomineralisation have been shown to influence rates of element uptake in otoliths of teleost species in some (but not all) manipulative experiments (Morales-Nin 2000;DiMaria et al 2010;Fablet et al 2011;Loewen et al 2016).…”
Section: Elementmentioning
confidence: 99%
“…cervical, thoracic, precaudal;Lewis et al 2017), among vertebrae within similar regions of the vertebral column (e.g. Lewis et al 2017;McMillan et al 2017a), with the exception of Zn (Raoult et al 2018), and little to no variation within similar regions of a vertebra (e.g. Tillett et al 2011;Smith et al 2016;Lewis et al 2017).…”
Section: Introductionmentioning
confidence: 99%